2022
DOI: 10.1155/2022/1981798
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells Alleviate Renal Fibrosis and Inhibit Autophagy via Exosome Transfer of miRNA-122a

Abstract: Exosomes derived from mesenchymal stem cell (MSC) alleviate kidney damage through autophagy. This study determined whether MSCs relieve renal fibrosis and inhibit autophagy by exosome transfer of miRNA-122a. The gene expression involved in the mTOR signaling pathway and autophagy was assessed in TGF-β1-treated human renal tubular epithelial cells (HK-2) and unilateral ureteral obstruction (UUO) mice before and after MSC-derived exosomes and miRNA-122a mimic treatment. Small RNA (sRNA) next-generation sequencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The authors determined that these effects were due to excreted exosomes mainly containing miRNA‐122. Inhibition of autophagy further strengthened the pathway of miRNA‐122‐to‐mTOR signalling and inhibited autophagy in tubular epithelial cells 26 …”
Section: Regulating Autophagymentioning
confidence: 96%
See 1 more Smart Citation
“…The authors determined that these effects were due to excreted exosomes mainly containing miRNA‐122. Inhibition of autophagy further strengthened the pathway of miRNA‐122‐to‐mTOR signalling and inhibited autophagy in tubular epithelial cells 26 …”
Section: Regulating Autophagymentioning
confidence: 96%
“…Inhibition of autophagy further strengthened the pathway of miRNA-122-to-mTOR signalling and inhibited autophagy in tubular epithelial cells. 26 In contrast, Yin et al found that BM MSC-derived exosomes prevented epithelial-mesenchymal transition (EMT) in tubular epithelial cells mediated by TGFβ1 through Nedd1L transport, thereby enhancing the occurrence of autophagy and mitigating the occurrence of RF. 27 These discrepant findings may be due to the properties of autophagy in each case.…”
Section: Regulating Autophagymentioning
confidence: 97%
“…For instance, Grange et al 121 found that EVs of MSCs can inhibit and reverse the progression of glomerular and tubule-interstitial fibrosis in the DN mouse models by downregulating fibrosis-related genes (eg, Serpia1a, TIMP1, MMP3, collagen I, and Snail). The MSCs-Exo inhibited the EMT process of transforming growth factor (TGF)-β1–treated renal tubular epithelial cells and renal fibrosis in a unilateral ureteric obstruction (UUO)–induced renal fibrosis mouse model via delivery of miRNA-122a 73 and miR-186-5p 82 . Liu et al 79 found that UCMSCs-Exo exhibits anti-fibrotic effects in CKD through the inactivation of the reactive oxygen species (ROS)–mediated p38 mitogen-activated protein kinases/extracellular signal-regulated kinase (MAPK/ERK) pathway.…”
Section: Efficacy and Mechanisms Of Mscs Therapy In Kdmentioning
confidence: 99%
“…In addition, it has been shown that let-7i-5p is a Smad3-dependent microRNA that promotes renal fibrosis in mice with unilateral ureteral obstruction, and let-7i-5p may be a promising gene therapeutic target for the treatment of renal fibrosis associated with CKD (chronic kidney disease) [ 59 ]. Li et al [ 60 ] found that mesenchymal stem cells reduced renal fibrosis through exosomes derived from mirNA-122a and inhibitd autophagy, and the export of mirNA-122a by mesenchymal stem cell-derived exosomes represents a new strategy to reduce obstructive renal fibrosis. The above-mentioned scholars' studies have shown that there are diverse gene therapy targets in treatment of obstructive renal fibrosis.…”
Section: Treatment Of Renal Interstitial Fibrosis In Obstructive Neph...mentioning
confidence: 99%